First-in-human phase I study of the bromodomain and extraterminal motif inhibitor BAY 1238097: emerging pharmacokinetic/pharmacodynamic relationship and early termination due to unexpected toxicity. (March 2019) - Postel-Vinay, Sophie; Herbschleb, Karin; Massard, Christophe; Woodcock, Victoria; Soria, Jean-Charles; Walter, Annette O.; Ewerton, Flavio; Poelman, Martine; Benson, Neil; Ocker, Matthias; Wilkinson, Gary; Middleton, Mark
Abstract: Background: Bromodomain and extraterminal motif (BET) protein inhibition is a promising cancer treatment strategy, notably for targeting MYC - or BRD4-driven diseases. A first-in-human study investigated the safety, pharmacokinetics, maximum tolerated dose and recommended phase II dose of the BET inhibitor BAY 1238097 in patients with advanced malignancies. Material and methods: In this phase I, open-label, non-randomised, multicentre study, patients with cytologically or histologically confirmed advanced refractory malignancies received oral BAY 1238097 twice weekly in 21-day cycles using an adaptive dose-escalation design at a starting dose of 10 mg/week. Model-based dose–response analysis was performed to guide dose escalation. Safety, pharmacokinetics, pharmacodynamics and tumour response were evaluated. Results: Eight patients were enrolled at three dose levels (10 mg/week, n = 3; 40 mg/week, n = 3; 80 mg/week, n = 2). Both patients receiving 80 mg/week had dose-limiting toxicities (DLTs) (grade 3 vomiting, grade 3 headache and grade 2/3 back pain). The most common adverse events were nausea, vomiting, headache, back pain and fatigue. Pharmacokinetic analysis indicated a linear dose response with increasing dose. Two patients displayed prolonged stable disease; no responses were observed. Biomarker evaluation of MYC and HEXIM1 expression demonstrated an emerging pharmacokinetic/pharmacodynamic relationship, with a trend towards decreased MYC and increased HEXIM1 expression in response to treatment. Conclusion: The study was prematurely terminated because of the occurrence of DLTs at a dose below targeted drug exposure. Pharmacokinetic modelling indicated that an alternate dosing schedule whereby DLTs could be avoided while reaching efficacious exposure was not feasible. Registration number: NCT02369029. Highlights: BET inhibition may be a promising therapeutic strategy for MYC -driven tumours. BAY 1238097 is a highly selective BET inhibitor known to suppress MYC expression. Severe toxicities at dose escalation led to phase I study termination. Pharmacokinetic simulations of a feasible alternate schedule were unsuccessful. Trends towards modulation of pharmacodynamic BET-inhibition biomarkers were observed.